Hubungan Self-Disclosure dengan Quarter-Life Crisis pada Mahasiswa Keperawatan - Diah Wulan Salwa Azahra; Wahyu Endang Setyowati; Betie Febriana (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examined the relationship between self-disclosure and quarter-life crisis among undergraduate nursing students at the Faculty of Nursing, Universitas Islam Sultan Agung Semarang. Using a quantitative cross-sectional design, data were collected from 213 final-year students through validated self-disclosure and quarter-life crisis questionnaires. Descriptive analysis showed that most respondents had moderate to high levels of self-disclosure and experienced quarter-life crisis at low to moderate levels. Bivariate analysis using the Chi-square test revealed a significant association between self-disclosure and quarter-life crisis (p < 0.05). Students with higher levels of self-disclosure were more likely to report lower levels of quarter-life crisis, whereas those with low self-disclosure tended to experience higher crisis intensity. These findings indicate that self-disclosure functions as a protective psychosocial mechanism that facilitates emotional regulation, adaptive coping, and access to social support during the transition to adulthood. The study highlights the importance of strengthening interpersonal communication skills and providing supportive counseling programs to reduce developmental distress among nursing students. Promoting healthy self-disclosure may contribute to better psychological adjustment and academic well-being in higher education settings.